Insights into subarachnoid hemorrhage: A comprehensive case series analysis (Indian Journal of Case Reports, 2024)
Subarachnoid hemorrhage (SAH) is a critical neurological emergency characterized by bleeding into the subarachnoid space, typically resulting from the rupture of intracranial aneurysms. SAH is associated with high morbidity and mortality rates, making it a subject of significant clinical interest and concern. This case series aims to explore a series of patients with SAH, shedding light on the diverse clinical presentations, management strategies, and outcomes, with the ultimate goal of improving our understanding of this complex condition and enhancing patient care.